Strategi Multi-Stakeholder Dalam Pencegahan Penebangan Hutan Tropis Di Aceh: Multi-Stakeholder Strategy in Preventing Tropical Deforestation in Aceh - Nafis, Hilman; Suganda, Delfi (Jurnal Silva Tropika, 2026)
ABSTRACT Tropical deforestation in Aceh has become a significant environmental issue due to its impacts on ecosystem degradation, biodiversity loss, and increased risk of disasters such as floods and landslides. The Leuser Ecosystem (KEL), a vital part of Aceh's forests, faces threats from illegal logging, forest encroachment, and land conversion. This study aims to explore multi-stakeholder strategies to prevent tropical deforestation in Aceh and to examine the roles of the Environment and Forestry Agency (DLHK), Forest Police (Polhut), Non-Governmental Organizations (NGOs), and the private sector in forest protection efforts. This study uses a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation studies involving various informants from DLHK, WALHI, HAkA, Forest Police, and the private sector. The results show that deforestation prevention is achieved through collaboration between actors in the form of forest patrols, the use of monitoring technologies such as Smart Patrol and GIS, policy advocacy, and social forestry-based empowerment. This collaboration has encouraged dialogue, communication, and a shared commitment to forest protection. However, its implementation still faces several challenges, including a limited number of Forest Rangers, the size of the forest area under surveillance, inadequate supporting facilities, and suboptimal law enforcement. The study concluded that multi-stakeholder strategies play a crucial role in preventing deforestation, but strengthened coordination, increased human resource capacity, and optimized monitoring technology are needed for more effective and sustainable protection of Aceh's tropical forests.   Keywords: Aceh tropical forest, collaborative governance, deforestation, forest protection, multi-stakeholder   ABSTRAK Deforestasi hutan tropis di Aceh telah menjadi isu lingkungan yang signifikan karena dampaknya terhadap degradasi ekosistem, hilangnya keanekaragaman hayati, dan peningkatan risiko bencana seperti banjir dan tanah longsor. Kawasan Ekosistem Leuser (KEL), bagian penting dari hutan Aceh, menghadapi ancaman penebangan ilegal, perambahan hutan, dan konversi lahan. Penelitian ini bertujuan untuk mengeksplorasi strategi multi-stakeholder untuk mencegah deforestasi hutan tropis di Aceh dan untuk meneliti peran Dinas Lingkungan Hidup dan Kehutanan (DLHK), Polhut (Polisi Hutan), Organisasi Non-Pemerintah (LSM), dan sektor swasta dalam upaya perlindungan hutan. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Data dikumpulkan melalui wawancara, observasi, dan studi dokumentasi yang melibatkan berbagai informan dari DLHK, WALHI, HAkA, Polhut, dan sektor swasta. Hasil penelitian menunjukkan bahwa pencegahan deforestasi dicapai melalui kolaborasi antar aktor dalam bentuk patroli hutan, penggunaan teknologi pemantauan seperti Smart Patrol dan GIS, advokasi kebijakan, dan pemberdayaan masyarakat berdasarkan kehutanan sosial. Kolaborasi ini telah mendorong dialog, komunikasi, dan komitmen bersama terhadap perlindungan hutan. Namun, implementasinya masih menghadapi beberapa tantangan, termasuk jumlah Polisi Hutan yang terbatas, luasnya area hutan yang dipantau, fasilitas pendukung yang tidak memadai, dan penegakan hukum yang kurang optimal. Studi ini menyimpulkan bahwa strategi multi-stakeholder memainkan peran penting dalam pencegahan deforestasi, tetapi penguatan koordinasi, peningkatan kapasitas sumber daya manusia, dan optimalisasi teknologi pemantauan diperlukan untuk perlindungan hutan tropis Aceh yang lebih efektif dan berkelanjutan.   Kata kunci: hutan tropis Aceh, collaborative governance, deforestasi, perlindungan hutan, multi-stakeholder